2011
DOI: 10.1021/cb100253e
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Cysteine 468 in Stat3 Defines a Novel Site for Therapeutic Development

Abstract: Stat3 is a latent transcription factor that promotes cell survival and proliferation and is often constitutively active in multiple cancers. Inhibition of Stat3 signaling pathways suppresses cell survival signals and leads to apoptosis in cancer cells, suggesting direct inhibition of Stat3 function is a viable therapeutic approach. Herein, we identify a small molecule, C48, as a selective Stat3-family member inhibitor. To determine its mechanism of action, we used site-directed mutagenesis and multiple biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Recently, it has been shown that alkylation of reactive cysteine residues in STAT3 is a potential novel strategy for direct inhibiting of STAT3 function. Alkylation of Cys-468 in the DNA binding domain by the compound C48 is shown to prevent DNA binding, and methyl-2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oate (CDDO-Me) prevented STAT3 dimerization by alkylation of Cys-259 (23,31). In addition, the reactive compound Stattic inhibits STAT3 by binding to multiple cysteine residues in unphosphorylated STAT3 as determined by mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that alkylation of reactive cysteine residues in STAT3 is a potential novel strategy for direct inhibiting of STAT3 function. Alkylation of Cys-468 in the DNA binding domain by the compound C48 is shown to prevent DNA binding, and methyl-2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oate (CDDO-Me) prevented STAT3 dimerization by alkylation of Cys-259 (23,31). In addition, the reactive compound Stattic inhibits STAT3 by binding to multiple cysteine residues in unphosphorylated STAT3 as determined by mass spectrometry analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With the reactive potential of galiellalactone toward biological nucleophiles in consideration, we were interested in investigating whether galiellalactone can alkylate STAT3 and thereby inhibit the DNA binding as there is precedence that direct covalent modification of STAT3 with small molecules (23,24) or through cysteine oxidation (25) can block the transcriptional activity of STAT3. The aim of the present study is to elucidate in more detail the mechanism of action of galiellalactone using human prostate cancer cells as a model.…”
mentioning
confidence: 99%
“…37,38 Additionally, a recent report showed that specific alkylation of Cys463 in Stat3 by virtual ligand screening derived compounds selectively blocked Stat3-DNA interaction. 39 The reactomics approach described here takes advantage of differential cysteine reactivity on the recombinant target protein within the constraints of our current library and allows systematic interrogation of cysteine-based hotspots in proteins thereby providing a strategy to identify novel points of alkylation with therapeutic potential. The successful identification of Cys255 as an allosteric hotspot capable of modulating HIF-1a/ ARNT PasB domain PPI validates feasibility of this approach in this challenging target space.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 has now been reported to be tyrosine, serine and threonine phosphorylated [10], acetylated [11], alkylated [12], methylated [13], ubiquitinated [14] and glutathionylated [15]. However, it is important to note that all of these modifications were identified using STAT3 protein purified from entire cells -therefore no knowledge of compartment specific modifications and/or combinations of modifications that may be critical to STAT3 activity is available.…”
Section: Transcriptional Activity Of Unphosphorylated Stat3mentioning
confidence: 99%